Richard Owen Scotland 1810, Indiana 1890 - Albjerg, Victor Lincoln (Founders Series, 1946)
Richard Dale Owen was born in 1810 in Scotland to a wealthy textile manufacturer and philanthropist. The youngest of eight children, Richard grew up at the family estate of Braxfield House, where he received his early education from private tutors. He would later go on to study chemistry, physics, and natural sciences, among other subjects, traveling between Scotland and Switzerland for his schooling.Owen arrived in the United States in 1828 to teach in New Haven, Indiana, where his father was running an experimental utopian community of happiness, enlightenment, and prosperity. He would later go on to be Indiana's second state geologist before enlisting in the army during both the Mexican-American War and the American Civil War. Colonel Owen took command of 4,000 Confederate prisoners at Camp Morton in Indianapolis, where he established new daily routines and rules for supervision of the prisoners. Under Owen's command, prisoners were allowed to read books and form glee clubs, theatrical groups, and sports teams. He also created a camp bakery staffed by prisoners that proved to be a substantial cost savings, allowing for above-average rations for the prisoners under his watch.After his military service came to an end, Owen continued to serve as a state geologist as well as becoming a professor at Indiana University, teaching chemistry, language, and natural philosophy. After failing to help secure IU as Indiana's land-grant school, Owen was recruited to help establish Purdue University, west of Lafayette. The board of trustees selected him to serve as the University's first president on August 13, 1872. However, Owen and the trustees disagreed on many early initiatives, including his focus on agriculture and push for more comfortable living arrangements for students.After less than two years serving as president, where he never drew a salary, Owen resigned his position and returned to teaching at Indiana University, until hearing problems caused him to retire in 1879. He spent his remaining years in New Harmony, where he conducted research and published several scientific papers until his tragic death caused by an accidental poisoning at the hand of a local pharmacist.